Improving Students' Conceptual Understanding in Islamic Education Learning Through Active Learning Approaches at SD Negeri 22 Batang Tuhur - Megawati, Irva (Indonesian Journal of Education and Social Humanities, 2024)
This study aims to improve students' conceptual understanding ability in Islamic religious education learning by using an active learning approach. This study is a classroom action research that uses four steps, namely planning, action, observation and reflection. The subjects of this study were high school students. The data of this study were obtained by test and observation techniques. Tests are used to measure learning outcomes and observations are used to analyze teacher and student learning activities. The data analysis technique used in this study is descriptive statistics by comparing the results obtained with indicators of research success. The results of the study indicate that an active learning approach can improve students' conceptual understanding ability in Islamic religious education learning. This can be seen from the increase in the percentage of student learning completion in each cycle with details of the pre-cycle 58.11%, the first cycle 73.19% and in the second cycle it increased to 89.36%. Thus, the use of an active learning approach can be used as an alternative to improve student learning outcomes in Islamic religious education learning.